Negative Exponents (Negative Indices)


Consider the following division:
$$\dfrac{3^2}{3^3} = 3^{2-3} = 3^{-1}$$
Now, if we attempt to calculate the value of this division:
$$\dfrac{3^2}{3^3} = \dfrac{9}{27} = \dfrac{1}{3}$$
From this conclusion we can say that $3^{-1} = \dfrac{1}{3}$.
This conclusion can be generalised:
$$a^{-1} = \dfrac{1}{a}$$

Example 1

Write $4^{-1}$ in fractional form.

Example 2

Write $\dfrac{1}{x}$ in exponent (index) form.


This rule can be extended for negative exponents (negative indices) other than $-1$.
Consider the expression $\dfrac{a^2}{a^5}$.
Using the exponent laws $\dfrac{a^2}{a^5} = a^{2-5} = a^{-3}$ and simplifying the fraction, we obtain
\( \begin{align} \displaystyle \require{cancel}
\dfrac{a^2}{a^5} &= \dfrac{\bcancel{a} \times \bcancel{a}}{\bcancel{a} \times \bcancel{a} \times a \times a \times a} = \dfrac{1}{a^3}. \\
\end{align} \)

Thus $a^{-3} = \dfrac{1}{a^3}$.
In general we are able to say:
$$a^{-n} = \dfrac{1}{a^n}$$

Example 3

Write $5^{-2}$ in fractional form.

Example 4

Write $\dfrac{1}{a^3}$ using negative exponents (negative indices).